Strategi Desain Organisasi Klinik dalam Menghadapi Perubahan Global - Felik Fernando Tanzil; Rinawati Rinawati (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to explore the organizational design strategy of clinics in facing global changes that increasingly demand adaptability, efficiency, and service quality improvement. The research was conducted using a descriptive qualitative method through interviews with three clinic staff who provided in-depth insights regarding internal adjustments to technological, managerial, and human resource aspects. The data were analyzed thematically to identify patterns of organizational adaptation in clinical settings. The results indicate that clinics have begun to implement a more flexible organizational structure, encourage digital transformation in service delivery, and improve employee competence through continuous training. Furthermore, the study found that the ability to manage human resources effectively and integrate digital systems plays a central role in sustaining performance amid global change. The findings contribute to understanding how small- and medium-scale health organizations can redesign their structures to remain competitive and responsive to dynamic external environments. In conclusion, organizational design strategies that emphasize agility, digital integration, and participatory leadership can enhance the resilience and sustainability of clinical institutions.